Gendered experiences of providing informal care for older people: a systematic review and thematic synthesis - Ioanna Zygouri; Fiona Cowdell; Avraam Ploumis; Mary Gouva; Stefanos Mantzoukas (BMC, 2021)
Abstract Background and purpose The caregiving's impact on informal carers' quality of life and gender-based stereotypes make older individuals' informal care a complex process for which our knowledge is still limited. The purpose of this review is to identify how gender relates to informal carers' experiences of providing care for people aged 60 years and over with mental and physical health needs by synthesising the available empirical data published between 2000 to 2020. Design and methods The systematic method for reviewing and synthesising qualitative data was performed using the PRISMA checklist and ENTREQ statement. The CASP tool was used to examine the quality of the included papers. Thematic synthesis was used as the methodological framework. Results This review produced two analytical themes, the impact of gender on the caregivers' labour and negotiating gender identity with self, society, and cultural norms. While informal caregivers share motivators, a linkage between traditional gender stereotypes impacts caregiving burden and coping strategies. Informal carers' experiences entail a constant pursuit of self-agency after acquiring the caregiver role. Cultural values and their intersection with gender appear to influence caregivers' healthy adjustment into their new caregiving identities. The flexibility to move beyond gender boundaries could mediate caregivers' negotiations between self and society on developing their new caregiving identity. Providing intensive informal primary care to older people affects both men's and women's mental and physical health. Gender ideals of the feminine nurturing role further disadvantage women as they determine the caregiving arrangements, the strategies and resources to sustain the caring burden, and the adaptability to experience their new caregiving role positively. Men appear more flexible to debate their hegemonic masculinity and defend their existence in the caregiving role. Conclusion and implications Transgressing gender lines and expanding gender possibilities can ease the caregiving burden and strengthen caregivers coping potentials. Health professionals can empower informal careers to challenge gender binaries and expand gender possibilities by intentionally injecting the language of diversity in caring information and caring processes. The review findings outline a path for research on gender identity development in older people's care.